The Concept and Functions of Performance Audit: Theoretical Study - Salienė, Asta; Tamulevičienė, Daiva; Gaižauskas, Lionius (Buhalterinės apskaitos teorija ir praktika, 2020)
Performance audit is a type of audit that evaluates and inspects an organizations’ activity based on the so-called 3E approach: economy, efficiency, effectiveness, and plays the most important role in institutions of public sector. During the implementation of the public sector reforms in recent decades, the concept of audit has been changing. Therefore, a need to re-evaluate the current definition of the audit and supplement it arose. It is also important to review the functions attributed to performance audit in order to define its ever-changing identity. The aim of the article: to evaluate the concepts of performance audit and the conceptual development of functions from a theoretical point of view. The article presents the analysis of performance audit concepts as well as a performance audit definition. The functions of performance audit have been distinguished, grouped, and evaluated based on how often they are mentioned in the literature. Two problems that make the implementation of the functions more challenging have been distinguished: contradictions among functions arise due to a diverse range of functions; due to versatility of the activity, the functions are difficult to evaluate, and measure and evaluation criteria are hard to establish.